2019
DOI: 10.1080/1331677x.2019.1696696
|View full text |Cite
|
Sign up to set email alerts
|

Innovativeness as a determinant of entrepreneurial orientation: analysis of the hotel sector

Abstract: This paper analyses entrepreneurial orientation as a composite formed of innovation, proactiveness and risk-taking. The empirical data for this study were gathered from a survey sent to hotel managers. The fieldwork was carried out between January and June 2018. The process provided 102 valid questionnaires. Two methods were used: structural equation modelling (PLS-SEM) and fuzzy-set qualitative comparative analysis (fsQCA). This study makes six key contributions and findings. First, the use of these two metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 76 publications
3
13
0
4
Order By: Relevance
“…As the indirect effect mediated by the IO factor is stronger than the direct effect between EO-Performance, we believe and in line to the findings of Pinho and Prange (2016) (Kilic, Ulusoy, Gunday, & Alpkan, 2015;Kyrgidou & Spyropoulou, 2013;Lintukangas, Kähkönen, & Hallikas, 2019). Rutherford and Holt (2007) and Hernández-Perlines et al (2019) underline innovativeness as the main key of the EO construct and are therefore in line with our findings; indeed, this has also been found to be the case in other Portuguese studies (Franco & Haase, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As the indirect effect mediated by the IO factor is stronger than the direct effect between EO-Performance, we believe and in line to the findings of Pinho and Prange (2016) (Kilic, Ulusoy, Gunday, & Alpkan, 2015;Kyrgidou & Spyropoulou, 2013;Lintukangas, Kähkönen, & Hallikas, 2019). Rutherford and Holt (2007) and Hernández-Perlines et al (2019) underline innovativeness as the main key of the EO construct and are therefore in line with our findings; indeed, this has also been found to be the case in other Portuguese studies (Franco & Haase, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Ferreira (2007) on the Portuguese economy. Moreover, even maintaining the core items (Hernández-Perlines et al, 2019;Rutherford & Holt, 2007), a more robust demonstration of the EO construct validity and/or reliability would be desirable; in fact, the two items related to risk had to be removed due to their low factor loadings and low individual reliability. This evidence indicates that Portuguese exporters display a high level of risk aversion.…”
Section: Discussionmentioning
confidence: 99%
“…We understand innovation as a firm’s ability to exploit knowledge and thereby generate new products, services, and processes ( McDowell et al, 2018 ). However, innovation always involves a certain amount of risk, which is why the results are not always satisfactory ( Hernández-Perlines et al, 2020 ).…”
Section: Absorptive Capacity and Innovationmentioning
confidence: 99%
“…However, literature recently began to use entrepreneurial orientation as an individual entrepreneur construct and sometimes referred to it as individual entrepreneurial orientation or intrapreneurial orientation (Koe, 2016;Schachtebeck et al, 2019). According to the reviewed literature, the most used proxies for entrepreneurial orientation have been innovativeness, proactiveness and risk-taking (Koe, 2016;Núñez-Pomar et al, 2016;Linton & Kask, 2017;Al Mamun et al, 2017;Hernández-Perlines et al, 2020). These studies have revealed that successful entrepreneurs often possess characteristics such as: the need for achievement, the ability to ensure locus of control, a high self-esteem, and an innovativeness capability (Abdul-Mohsin et al, 2012).…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
“…These studies have revealed that successful entrepreneurs often possess characteristics such as: the need for achievement, the ability to ensure locus of control, a high self-esteem, and an innovativeness capability (Abdul-Mohsin et al, 2012). Other variables that have been used in past works to capture entrepreneurial orientation include: having self-confidence, being committed to completing tasks, having an extensive network of friends and colleagues, eagerness to use new technologies, searching for new opportunities, and being resilient (Koe, 2016;Randerson, 2016;Wales, 2016;Al Mamun et al, 2017;Barba-Sánchez & Atienza-Sahuquillo, 2018;Hernández-Perlines et al, 2020). Hence, the present study used the variables explored in previous studies listed above.…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%